PSA negative cerebellar metastasis from prostate cancer: a case report - Pecoraro, Michele Federico; Marengo, Nicola; Senetta, Rebecca; Calamo Specchia, Francesco; Pittaro, Alessandra; Ducati, Alessandro; Garbossa, Diego (European Journal of Oncology and Environmental Health, 2015)
Brain metastases from prostate cancer are very rare. We report an unusual case of PSA-negative cerebellar metastasis in a 77-year-old man with known prostate cancer since 2003 and negative clinical and radiological follow-up for the following 10 years. The lesion was discovered during the radiological follow-up for his pre-existent cerebrovascular disease; at first the patient was completely asymptomatic and only after one year began to complain of symptoms related to the area involved rather than the mass-effect. Beside the highly unusual cerebellar site, another peculiarity is the lack of rise in PSA serum level and the cerebellum as the only and first site of distant spread. This suggests a particular type of cancer behavior with direct brain occurrence via the paravertebral venous plexus draining from the prostate, and a relatively benign growth; for some still unknown reason this has happened without a significant PSA increase. The case reported also suggests that in a patient with prostate carcinoma without any other secondary involvement but with even mild neurological symptoms, a brain imaging study should always be performed.